2014
DOI: 10.1016/j.scitotenv.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Fish eyes and brain as primary targets for mercury accumulation — A new insight on environmental risk assessment

Abstract: Fish eyes and brain are highly susceptible to environmental Hg exposure but this issue is still scarcely investigated, mainly regarding methylmercury (MeHg) accumulation. Yet, Hg levels in fish lens have not been previously examined under field conditions. Total Hg (tHg), MeHg and inorganic Hg (iHg) levels were assessed in the brain, eye wall and lens of the golden grey mullet (Liza aurata) from an Hg contaminated area, both in winter and summer, together with water and sediment levels. Sampling was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 41 publications
6
67
1
1
Order By: Relevance
“…Inter-site differences of Hg were mostly found in the sediment, suggesting that this compartment is the main source of Hg to mullets. Results obtained in this study are in line with other studies performed at Ria de Aveiro revealing a higher accumulation of Hg in L. aurata liver from LAR in comparison to individuals caught at R (Guilherme et al, 2008;Mieiro et al, 2009;Pereira et al, 2014). The partitioning of tHg among the four sub-cellular fractions varied between individuals from R and LAR.…”
Section: Introductionsupporting
confidence: 91%
“…Inter-site differences of Hg were mostly found in the sediment, suggesting that this compartment is the main source of Hg to mullets. Results obtained in this study are in line with other studies performed at Ria de Aveiro revealing a higher accumulation of Hg in L. aurata liver from LAR in comparison to individuals caught at R (Guilherme et al, 2008;Mieiro et al, 2009;Pereira et al, 2014). The partitioning of tHg among the four sub-cellular fractions varied between individuals from R and LAR.…”
Section: Introductionsupporting
confidence: 91%
“…It has an inner basin, the Laranjo Basin, located near Estarreja, Portugal (Fig. [2][3][4] As a result of the absence of other important sources of contaminants, Laranjo Basin is considered to be a field laboratory offering a unique opportunity to assess Hg toxicity under realistic conditions. The high levels of contamination resulted from five decades of continuous discharges from a chlor-alkali plant, which generated a contamination gradient for Hg.…”
Section: Study Areamentioning
confidence: 99%
“…Both sites were selected based on previous ecotoxicological studies [2][3][4]18 (Fig. Both sites were selected based on previous ecotoxicological studies [2][3][4]18 (Fig.…”
Section: Samplingmentioning
confidence: 99%
“…High levels of Hg are still stored in sediments [Coelho et al, 2005] and could be found in the biota [Guilherme et al, 2008a;Mieiro et al, 2010;Pereira et al, 2013]. Due to the absence of other important sources of contaminants, Largo do Laranjo is considered a ''field laboratory", offering a unique opportunity to assess Hg toxicity under realistic conditions [Guilherme et al, 2008a;Mieiro et al, 2010;Pereira et al, 2014]. São Jacinto is located near the lagoon entrance, about 10 km from Largo do Laranjo.…”
Section: Study Area Characterizationmentioning
confidence: 99%
“…It was demonstrated that Hg may target the eyes under environmental exposures [Pereira et al, 2013[Pereira et al, , 2014 and that MeHg is preferentially accumulated in the eyes in comparison with other key organs such as liver [Korbas et al, 2012[Korbas et al, , 2013. A recent innovative study showed that MeHg accumulates in the secondary lens fibers immediately underlying the lens epithelial cells [Korbas et al, 2013].…”
Section: Introductionmentioning
confidence: 99%